Disability costs and equivalence scales in the older population - Marcello Morciano; Ruth Hancock; Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2012)
We estimate the implicit disability costs faced by older people, using data on over 8,000 individuals from the UK Family Resources Survey. We extend previous research by using a more flexible statistical modelling approach and by allowing for measurement error in observed disability and standard of living indicators. We find that disability costs are strongly related to the severity of disability and to income and - at an average level of almost 100 per week among over-65s with significant disability - they typically far exceed the value of any state disability benefits received.
Keywords: C81; D1; I1; 330; costs of disability; disability indexes; standard of living; equivalence scale; structural equation modelling